Global Longitudinal Strain is Incremental to Left Ventricular Ejection Fraction for the Prediction of Outcome in Optimally Treated Dilated Cardiomyopathy Patients - Raafs, Anne G.; Boscutti, Andrea; Henkens, Michiel T. H. M.; van den Broek, Wout W. A.; Verdonschot, Job A. J.; Weerts, Jerremy; Stolfo, Davide; Nuzzi, Vincenzo; Manca, Paolo; Hazebroek, Mark R.; Knackstedt, Christian; Merlo, Marco; et al. (Journal of the American Heart Association, 2022)
Background Speckle tracking echocardiographic global longitudinal strain (GLS) predicts outcome in patients with new onset heart failure. Still, its incremental value on top of left ventricular ejection fraction (LVEF) in patients with nonischemic, nonvalvular dilated cardiomyopathy (DCM) after optimal heart failure treatment remains unknown. Methods and Results Patients with DCM were included at the outpatient clinics of 2 centers in the Netherlands and Italy. The prognostic value of 2-dimensional speckle tracking echocardiographic global longitudinal strain was evaluated when being on optimal heart failure medication for at least 6 months. Outcome was defined as the combination of sudden or cardiac death, life-threatening arrhythmias, and heart failure hospitalization. A total of 323 patients with DCM (66% men, age 55±14 years) were included. The mean LVEF was 42%±11% and mean GLS after optimal heart failure treatment was -15%±4%. Twenty percent (64/323) of all patients reached the primary outcome after optimal heart failure treatment (median follow-up of 6[4-9] years). New York Heart Association class ≥3, LVEF, and GLS remained associated with the outcome in the multivariable-adjusted model (New York Heart Association class: hazard ratio [HR], 3.43; 95% CI, 1.49-7.90, =0.004; LVEF: HR, 2.13; 95% CI, 1.11-4.10, =0.024; GLS: HR, 2.24; 95% CI, 1.18-4.29, =0.015), whereas left ventricular end-diastolic diameter index, left atrial volume index, and delta GLS were not. The addition of GLS to New York Heart Association class and LVEF improved the goodness of fit (log likelihood ratio test <0.001) and discrimination (Harrell's C 0.703). Conclusions Within this bicenter study, GLS emerged as an independent and incremental predictor of adverse outcome, which exceeded LVEF in patients with optimally treated DCM. This presses the need to routinely include GLS in the echocardiographic follow-up of DCM.